Left Coronary Artery—Right Ventricle Fistula Case Report: Optimal Treatment Decision - Stefan Veljković; Ana Peruničić; Jovana Lakčević; Armin Šljivo; Dragana Radoičić; Mihajlo Farkić; Darko Boljević; Jelena Kljajević; Milovan Bojić; Aleksandra Nikolić (Medicina)
Coronary artery fistulas (CAFs) are rare congenital anomalies, presenting in 0.05–0.9% of cases, characterized by an aberrant connection between a coronary artery and a cardiac chamber or great vessel. Clinical manifestations can include heart failure, myocardial ischemia due to coronary steal, arrhythmias, or infective endocarditis. We report a case of a 39-year-old man initially evaluated in 2016 for peripheral edema and suspected right ventricular (RV) abnormality. Earlier assessments indicated a left anterior descending (LAD) coronary artery–RV fistula, but initial catheterization was nondiagnostic. Transthoracic echocardiography (TTE) revealed a dilated left coronary artery (LCA) and an RV apex aneurysm, confirmed by CT and coronary angiography, showing a 14 mm LAD fistula with large aneurysmal sacs (45.6 × 37.3 mm). Cardiac MRI demonstrated a tortuous LAD fistula draining into RV aneurysmal sacs with preserved biventricular function. Surgical intervention was recommended, but the patient declined and was lost to follow-up until 2022, being asymptomatic. Re-evaluation showed progression in aneurysm size (47 × 45 mm and 16 × 18 mm) without ventricular functional change. Follow-up TTE in 2023 indicated stable findings. This case emphasizes the necessity of multimodal imaging (TTE, CT, MRI, angiography) for CAF diagnosis and management planning. Given the variability in CAF presentation and outcomes, individualized management—including surgical, percutaneous, or conservative strategies—is crucial. Persistent follow-up is essential for monitoring potential complications and guiding treatment, even in asymptomatic patients refusing intervention.